Personality Competency of Fiqh Teachers Shapes Student Worship Discipline - Bitri Hariani Lubis; Enny Nazrah Pulungan (Academia Open, 2025)
General background: Student worship discipline is shaped not merely by cognitive understanding of fiqh but significantly by the teacher's personal example and moral integrity. Specific background: Despite the critical role of teacher personality in Islamic education, empirical studies exploring how personality competence affects students' worship behavior remain limited. Knowledge gap: Little is known about the specific personality traits and contextual factors that enable fiqh teachers to effectively cultivate worship discipline in students. Aims: This study investigates the personality competence of fiqh teachers in shaping student worship discipline at MTs GUPPI Pangkatan. Results: Using a qualitative descriptive approach and triangulated data from interviews, documents, and literature, the findings reveal that effective fiqh teachers exhibit stable, mature, wise, and morally exemplary personalities, coupled with strong religious commitment and authority. Novelty: The study identifies internal (teacher personality and commitment) and external (curriculum, method, environment, parental and principal support) factors that support or inhibit success, highlighting the interplay between personal competence and institutional context. Implications: These findings suggest that enhancing teacher personality competence should be prioritized in teacher training programs to foster disciplined religious practices among students. Highlights: Teacher personality directly influences students' worship discipline. Internal and external factors shape teaching effectiveness. Moral integrity is essential for religious education success. Keywords: Personality Competence, Fiqh Teacher, Worship Discipline, Islamic Education, Student Behavior